APLIKASI MENENTUKAN NILAI POLYPROPYLENE RASIO BERBASIS WEB DI PT.TBINA - Hidayat, Khusnul; Setyowibowo, Sigit (DINAMIKA DOTCOM, 2017)
One supporter of the success of a manufacturing industry that is viewed in terms of the quality of products produced by the company. Therefore, in any production process is necessary to check the quality from raw material to finished product prior to the hands of consumers. One of them is the process of calculating the ratio of raw material mixture before used as a finished product. In PT. TBINA process is done automatically by the machine by setting Â¬nilai mixture ratio set on the machine. However, the actual results of the process can not be known directly by production operators . This is due to the phase of the sample test on the products that are being produced where the stage takes 4 hours . As a result , the status of stock products production is unclear whether the product is defective or not the resulting product can not be continued to the next process. Required application that is able to predict the outcome of the actual ratio value directly without having to wait for the test results of samples which takes 4 hours . These applications can help the production process goes smoothly . Implementation of the application is made with PHP , so to run it can use a browser application that has installed a computer.Â Key Word: Aplication, Web, Polypropylene Ratio, TBINA